Electromechanical stability, electrochemical energy storage, and mechano-electrochemical energy harvesting of carbon nanotube buckles. (1st May 2023) - Yu, Seongjun; Son, Wonkyeong; Jeon, Gichan; Kim, Jeeeun; You, Jeewon; Ko, Sunho; Choi, Changsoon
Abstract: Compared with the traditional two- or three-dimensional devices, one-dimensional (1D) coiled carbon nanotube (CNT) yarn-based devices can offer several advantages for wearable, downsizing, and implantable applications. However, coiled CNT yarns still exhibit several significant drawbacks, including structural instability. We propose micro-scale CNT buckled core-sheathed fibers with electrochemical multifunctionalities, including electromechanical stability, wearable supercapacitor application, and energy harvesting ability, to overcome the limitations of 1D coiled CNT yarns. These fibers maintain their electrical performance even under high stretchability conditions without any critical resistance change (less than 10%) because of the high stability of the CNT buckles (∼600% tensile strain). In addition, these CNT buckled fibers exhibit improved capacitances (higher than those of the non-buckled structures) and can mechano-electrochemically generate electrical energy under a directed tensile strain (open-circuit voltage peak ∼ 0.6 mV at 4 Hz and 300% strain). Such multifunctional CNT buckle fibers hold great prospects in numerous applications, including stretchable electrodes, energy storage, and energy harvesting. Graphical abstract: The CNT buckled core sheath (CBCS) fibre exhibit electrochemical multifunctionalities, including electromechanical stability, supercapacitor, and energy harvesting ability and can thus overcome the limitations of 1D coiled CNT yarns. The electrochemical multifunctionalities are maintained under high stretchability conditions without critical resistance change because of the CNT buckles' stability. The CNT buckled fibres improve the capacitance, compared with that of the structure without buckle configurations, as well as generates electrical energy via a mechano-electrochemical mechanism through tensile direction strain. Image 1 Highlights: The CBCS fibers have electromechanical stability, electrochemical energy storage, and mechano-electrochemical energy harvesting. It stably maintains 600% stretchability using delaminated buckle structure. The delaminated buckle surface on CBCS fibers can improve capacitance through additional active EDL site. The CBCS fiber showed energy harvesting via tensile actuation.